Risk modification of colorectal cancer susceptibility by interleukin-8 -251T>A polymorphism in Malaysians - Mohd Aminudin, Mustapha; Siti Nurfatimah, Mohd Shahpudin; Ahmad Aizat, Abdul Aziz; Ankathil, Ravindran (Baishideng, 2012)
AIM: To investigate the allele and genotype frequencies and associated risk of interleukin (IL )-8 -251T>A polymorphism on colorectal cancer (CRC) susceptibility risk. METHODS: Peripheral blood samples of 255 normal controls and 255 clinically and histopathologically confirmed CRC patients were genotyped for IL-8 -251T>A polymorphism employing allele-specific polymerase chain reaction. The relative association of variant allele and genotypes with CRC susceptibility risk was determined by calculating the odds ratios (ORs). Corresponding χ 2 tests on the CRC patients and controls were carried out and 95% confidence intervals (CIs) were determined using Fisher’s exact test. The allele frequencies and its risk association were calculated using FAMHAP, haplotype association analysis software. RESULTS: On comparing the frequencies of genotypes of patients and controls, the homozygous variant AA was significantly higher in CRC patients (P = 0.002) compared to controls. Investigation on the association of the polymorphic genotypes with CRC susceptibility risk, showed that the homozygous variant IL-8 -251AA had a significantly increased risk with OR 3.600 (95% CI: 1.550-8.481, P = 0.001). In the case of allele frequencies, variant allele A of IL-8 -251 showed a significantly increased risk of CRC predisposition with OR 1.32 (95% CI: 1.03-1.69, P = 0.003). CONCLUSION: Variant allele and genotype of IL-8 (-251 T>A) was significantly associated with CRC susceptibility risk and could be considered as a high-risk variant for CRC predisposition.